Pengembangan Media VR-LADUSI Berbasis Artsteps.com Untuk Meningkatkan Hasil Belajar Literasi Bahasa Indonesia Kelas II Sekolah Dasar - Wahyu Utami; Ika Ratnaningrum (STKIP Singkawang, 2025)
Technology-based learning media is increasingly needed in basic education, including virtual reality media to improve student learning outcomes. This study aims to develop, evaluate the feasibility and effectiveness of VR-LADUSI (Virtual reality-Exploring the World of Professions) media based on artsteps.com in Indonesian Class II. This research is based on the research and development (R&D) method with the ADDIE approach. Data collection techniques include interviews, observations, documentation, questionnaires, and tests. The results of the feasibility test are very feasible from the validation of media experts and material experts with a score of 96% and 89%. As well as questionnaires of student and teacher responses with scores of 92% and 83% which support the feasibility of the media. VR-LADUSI media is effective in improving language literacy learning outcomes with a sig value of 0.000 < 0.05 and t count 4.320 > t table 2.074. As well as N-Gain average score of 0.33 with moderate category. This study can be concluded that VR-LADUSI media was successfully developed, very feasible to use, and effective for improving language learning outcomes. This research supports the importance of using technology-based learning media to attract students' interest so as to improve learning outcomes and add insight into the development of technology-based media in basic education.